Przemiany opiekuńczo-wychowawczego środowiska rodziny z dzieckiem niepełnosprawnym – przeszłość i teraźniejszość - Apanel, Danuta (Karkonoska Państwowa Szkoła Wyższa, 2011)
This study outlines changes in an environment of a family upbringing a disabled child in various historical ages, including sources of those changes. The source of mentioned changes were mostly: the level of a social development, the level of its culture, religious beliefs, norms and customs, political and economical situation, as well as the level of scientific and technical development. The study includes also the most representative examples depicting a social situation of such families, starting from ancient Greece and Rome, thrughmiddle ages, renaissance until the time of the French Revolution. Next comes difficult times of the 19 century,which worsened the situation of those families. On the other hand, however it brought significant progress to the science, especially to biology, psychology, medicine and pedagogic. It has a big impact on changes in disabled people situation. The 20 introduced various and major changes. From the one side it brought hope for alleviating the situation of the family with disabled child, from the other tragic times of the Second World War and rapiddevelopment of segregation forms in education and care for disabled people in PRL. After political changeover, however one can observe positive tendencies. But there are still significant requirements for social education in order to normalize their life in terms of the disabled and their families' needs.
Keywords: rodzina; opieka; edukacja; niepełnosprawni; dzieci